"It's crazy being a Black, gay youth." Getting information about HIV prevention: A pilot study. Issue 1 (4th December 2012) - Voisin, Dexter R.; Bird, Jason D.P.; Shiu, Cheng‐Shi; Krieger, Cathy
ABSTRACT: Background: Access and adoption of HIV prevention information are important criteria for reducing HIV infection rates among men who have sex with men. Methods: Using focus group data, researchers sought to identify sources of HIV prevention information and barriers to adopting protective behaviors among young African American men who have sex with men. Adolescents ages 18–24 were recruited for this study. Focus group data were analyzed to identify themes related to sources of HIV prevention information and barriers to adopting protective behaviors. Results: Researchers documented that family and friends, formal education, television, and the LGBT community were major sources for HIV prevention information. However, motivation for adopting such information was hampered by apathy, homophobia, and racism. Conclusion: Feelings of powerlessness need to be addressed when targeting Black MSM with HIV prevention information.